Integrating Breathing Techniques Into Psychotherapy to Improve HRV: Which Approach Is Best? - Steffen, Patrick R.; Bartlett, Derek; Channell, Rachel Marie; Jackman, Katelyn; Cressman, Mikel; Bills, John; Pescatello, Meredith (Frontiers in Psychology, 2021)
INTRODUCTION: Approaches to improve heart rate variability and reduce stress such as breathing retraining are more frequently being integrated into psychotherapy but little research on their effectiveness has been done to date. Specifically, no studies to date have directly compared using a breathing pacer at 6 breaths per minute with compassion focused soothing rhythm breathing. CURRENT STUDY: In this randomized controlled experiment, 6 breaths per minute breathing using a pacer was compared with compassion focused soothing rhythm breathing, with a nature video being used as a control group condition. METHODS: Measures of HRV and BP were measured. Following a 5-minute baseline, participants engaged in either 6 breath per minute breathing, soothing rhythm breathing, or watched a nature video for 10 minutes. Participants then wrote for 5 minutes about a time they felt intensely self-critical. Participants then wrote for 5 minutes about a time they felt self-compassionate, and the experiment ended with a 10-minute recovery period. RESULTS: Conditions did not significantly differ at baseline. Overall, HRV, as measured by SDNN, LF HRV, and LF/HF ratio, increased during the intervention period, decreased during self-critical writing, and then returned to baseline levels during the recovery period. HF HRV was not impacted by any of the interventions. Time by Condition analyses revealed that both the 6 breaths per minute pacer and soothing breathing rhythm conditions lead to significantly higher SDNN than the nature video condition during breathing practice but there were no significant differences between conditions in response to the self-critical and self-compassionate writing or recovery periods. The 6 breath per minute pacer condition demonstrated a higher LF HRV and LF/HF ratio than the soothing rhythm breathing condition, and both intervention conditions had a higher LF HRV and LF/HF ratio than the nature video. CONCLUSIONS: Both 6 breath per minute breathing and soothing rhythm breathing effectively increase heart rate variability as measured by SDNN, whereas the 6 breath per minute breathing led to the highest LF HRV and LF/HF ratio. Both breathing approaches impact HRV more than a nature video and can potentially be used as key adjuncts in psychotherapy in regulating physiological functioning.